Synthesis of 1H-pyrazolo[1,2-b]phthalazine-5, 10-dione derivatives using Hercynite magnetic nanocatalyst - Zahra Paknejadi; Hassan Kefayati (شیمی کاربردی روز)
Pyrazolophthalazines and their derivatives are known as a substance with diverse chemical and biological activity. These compounds have various medicinal properties such as anti-bacterial, anti-viral, anti-coagulant and anti-cancer. In this research synthesis of Pyrazolo-phthalazine derivatives by reaction of aromatic aldehyde derivatives, Phthalic hydrazide and malononitrile in the presence of Hercynite as nano-catalyst were studied and the products were obtained in 45-90 minutes with yield of 90-97%. The structure of Hercynite nanocatalyst was investigated using FT-IR and SEM methods and X-ray diffraction pattern. The results of the morphology of the nanocatalyst surface show that the nanoparticles are spherical and the size of the particles is between 49-80 nm. Investigating the magnetic property of the catalyst with VSM analysis shows the favorable magnetic property of Hercynite nanocatalyst for its separation with an external magnetic field. Easy operation, high efficiency, reuse of the catalyst for several times, short reaction time and easy separation of the catalyst using an external magnet are the most important advantages of the presented method.